Microacoustic Metagratings at Ultra‐High Frequencies Fabricated by Two‐Photon Lithography (Adv. Sci. 20/2022). Issue 20 (15th July 2022) - Melnikov, Anton; Köble, Sören; Schweiger, Severin; Chiang, Yan Kei; Marburg, Steffen; Powell, David A.
Abstract : Microacoustic Metagratings In article number 2200990, Anton Melnikov and co‐workers present microacoustic metagratings for passive wavefront manipulation of ultra‐high frequency ultrasound. The designs are created with topology and shape optimization techniques by incorporating the thermoviscous effects, and manufactured with two‐photon lithography. The successful experimental demonstration of the effectiveness of the designs opens a new route for acoustic metamaterials in ultrasonic applications with high spatial resolution.